Water resources systems - Bhave, Pramod R. (Alpha Science International, 2011)
Deals with comprehensive planning, analysis, design and management of river basins. In this book, essential principles of hydrology, hydraulics and probability together with optimization techniques and economic analysis are covered. It includes a list of relevant Indian standard.